Large-Scale Morphological Network Efficiency of Human Brain: Cognitive Intelligence and Emotional Intelligence - Li, Chunlin; Qiao, Kaini; Mu, Yan; Jiang, Lili (Frontiers in Aging Neuroscience, 2021)
Network efficiency characterizes how information flows within a network, and has been used to study the neural basis of cognitive intelligence in adolescence, young adults, and elderly, in terms of human brain white matter and functional connectivity networks. But there were few studies investigating whether human brain at different ages exhibited different underpins of cognitive and emotional intelligence from young adults to middle-aged, especially in terms of human brain morphology similarity networks. In this study we used 65 data (aging 18-64) including sMRI and behavioral measurements to study the associations of network efficiency with cognitive intelligence and emotional intelligence in young adult and middle-aged group. We proposed a new method of defining human brain morphological network using morphological distribution similarity (including cortical volume, surface area and thickness). Our results showed inverted age×network efficiency interactions in the relationship of surface area network efficiency with cognitive and emotional intelligence: a negative age×global efficiency (nodal efficiency) interactions in cognitive intelligence, while a positive age×global efficiency (nodal efficiency) interactions in emotional intelligence. In summary, our study not only proposed a new method of morphological similarity network, but also emphasized the developmental effects on brain mechanisms of intelligence from young-adults to middle-aged, and may promote mental health study on middle-aged in the future.